Germination and biochemical changes in ‘Formosa’ papaya seeds treated with plant hormones - Rafael Fonsêca Zanotti; Denise Cunha Fernandes dos Santos Dias; Raimundo Santos Barros; Fábio Murilo DaMatta; Glauter Lima Oliveira (Acta Scientiarum: Agronomy, 2014)
This study aimed to investigate the effects of growth regulators on germination rates and biochemical compound concentrations in Carica papaya L. seeds (‘Formosa’ group). The seeds were harvested from fruits at maturation stages 3 and 5 (50 and 75% yellow fruit skin, respectively). The effects of 2-chloroethylphosphonic acid (CEPA), KNO3 and gibberellic acid (GA3)on seed germination, germination index speed, soluble sugars, starch, lipids, soluble proteins and total proteins of the papaya seeds were evaluated. The seeds from stage 5 showed a higher rate of germination 30 days after sowing than did the seeds from stage 3. Treatment with CEPA decreased seed germination, apparently due to decreased starch mobilization; the opposite response was observed following KNO3 treatment. GA3, alone or in combination with KNO3, stimulated an increase in lipid mobilization. In general, with the exception of CEPA, all growth regulators tested were effective in overcoming seed dormancy, and KNO3 was the most effective. The seeds from stage 3 fruits treated with KNO3 or KNO3 + GA3 had higher rates of germination at 14 days.